MULTI-AGENT DECISION SUPPORT SYSTEMS BASED ON PRECEDENTS AND USING ADAPTIVE ONTOLOGIES - Litvin, V. V. (Radio Electronics, Computer Science, Control, 2024)
Methods of developing and functioning multi-agent solution support systems based on precedents and using adaptive ontology which are the part of intelligent agents are analyzed. The method of distance definition between the precedent and current situation based on adaptive ontology is developed.